Information System of Plan Maintenance System (PMS) Based on Android Application - Syamsadhiyak, Nawan Gilang; Hermanto, Andy Wahyu; Safi’i, Imam (Dinamika Bahari, 2025)
The density of shipping activities today, every ship must have machinery that is always in good condition. Therefore, the implementation of maintenance on every machinery on the ship is very important. However, according to reality, many machinists or engineers do not pay attention to the importance of maintenance on machinery. The machinery maintenance system or Plan Maintenance System (PMS) is a routine maintenance schedule for existing machinery on the ship so that its condition remains optimal. Researchers took the title of this study because they wanted to increase their understanding of the importance of routine maintenance of machinery on ships so that the machinery continues to work optimally. Researchers developed from the importance of maintenance and associated with the application of informatics techniques so that researchers wanted to design an application that functions for an android-based Plan Maintenance System information system that can be used as a maintenance reminder and engine maintenance results. Researchers used the Research and Development method to complete the research conducted with the development of Borg and Gall with the development of 10 steps, but researchers only took 9 steps because researchers did not make products in bulk. The 9 steps are the potential problem stage, information gathering, initial product design, product trial I, product revision I, design validation, product revision II, product trial II, and final product finalisation. The results of the research on making the android-based Plan Maintenance System information system application can be done using all types of computers that have Native Script installed to do the application coding process. This Plan Maintenance System application can be used by cadets of the Semarang Polytechnic of Shipping Science and Engineers who are on board as a means of knowledge and as an information system regarding maintenance of machinery spare parts